Development of an eco-literacy based learning model to promote sustainable practices in elementary schools - Suprayitno Suprayitno; Hitta Alfi Muhimmah; Nurhayati Mawaddah; Supriyanto Supriyanto; Syariffanor binti Hisman (Universitas Negeri Surabaya, 2026)
This study addresses the limited integration of environmental sustainability and disaster preparedness in primary education, particularly in environmentally vulnerable coastal areas. It aims to develop and evaluate an integrated sustainability learning model implemented through the Sekolah Nyawiji Program. The study employed a research and development design using the define, design, develop, and disseminate stages. Data were collected through expert validation, user responses, and pre-test–post-test assessments.The results show that the model achieved high validity, with expert validation scores ranging from 3.50 to 4.00, indicating strong alignment between design and learning objectives. The model also demonstrated good practicality, reflected in high usability based on teacher and student responses. In terms of effectiveness, the model produced a high N-Gain score of 0.76, indicating substantial improvement in students’ learning outcomes. These findings demonstrate that contextual and place-based sustainability learning enhances ecological understanding, environmental responsibility, and disaster preparedness. The study concludes that integrating eco-literacy, responsible consumption, and coastal ecosystem awareness provides an effective and applicable framework for sustainability learning in primary education.